Механізми інотропних ефектів бальнеотерапії на курорті Трускавець - Ружило, С.В.; Попович, І.Л.; Білас, В.Р. (Медична гідрологія та реабілітація, 2004)
It is shown that cardinal parameter of hemodynamic - index of contractility of myocard (ICRP) - is realized by means of tonic regulatory adrenergic and cholinergic nervous influences and activity of Na+, K+- ATPase. It is detected strophantindependent and strophantinindependent types of adrenergic and cholinergic regulation of inotropism in various persons. The belonging of definite type is determined by constellation of antromometic hemodynamic, veloergometric, regulatory and metabolic parameters and are prognozed by method of disccriminant analysis (correctly 96%).